Recent psychopathology, suicidal thoughts and suicide attempts in households with and without firearms: findings from the National Comorbidity Study Replication. Issue 3 (3rd June 2009) - Miller, M; Barber, C; Azrael, D; Hemenway, D; Molnar, B E
Abstract : Objective: To assess the relationship between firearm ownership and possible psychiatric confounders of the firearm–suicide relationship. Methods: Multivariate logistic regression was used to estimate the association between living in a home with firearms and 12-month occurrence of major Diagnostic and statistical manual of mental disorders (DSM)-IV disorders and suicidal behaviour among respondents to the National Comorbidity Survey Replication, a household survey of 9282 adults aged 18+. Analyses controlled for sociodemographic characteristics including age, sex, race/ethnicity, educational attainment and poverty. Results: Approximately one in three Americans reported living in a home with firearms. People living in a home with firearms were no more or less likely than people in homes without firearms to have recent (past year) anxiety disorders (OR = 1.0, 95% CI 0.8 to 1.2), mood disorders (OR = 0.9, 95% CI 0.7 to 1.1) or substance dependence and/or abuse (OR = 0.9, 95% CI 0.6 to 1.3). Past year suicidal ideation (OR = 0.8, 95% CI 0.5 to 1.3) and suicide planning (OR = 0.5, 95% CI 0.2 to 1.4) were also not associated with living in households with firearms. Having made a suicide attempt over the previous year was the only outcome more common among participants reporting that they currently lived in a home with firearms. Conclusions: The previously reported association between household firearm ownership and heightened risk of suicide is not explained by a higher risk of psychopathology among gun-owning families. As there are Americans with suicidal ideation and/or significant and recent psychiatric disorders currently living in homes with firearms, future work should focus on understanding the impediments to effectively communicating the suicide risk associated with household firearms.